Tanks - Hogg, Ian V., 1926-2002.; Sarson, Peter; Bryan, Tony (Minneapolis : Lerner, 1985)
A survey of the evolution of modern armored tanks, now equipped with computerized electronics, night vision, air filtration, and laser fire control systems, and their tasks and tactics today.
Includes index.
Keywords: Military tanks; Tanks (Military science)